2014
DOI: 10.20506/rst.33.3.2328
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological survey on Rift Valley fever among small ruminants and their close human contacts in Makkah, Saudi Arabia, in 2011

Abstract: This study describes a seroepidemiological survey on Rift Valley fever (RVF) among small ruminants and their close human contacts in Makkah, Saudi Arabia. A total of 500 small ruminants (126 local, 374 imported) were randomly selected from the sacrifice livestock yards of Al-Kaakiah slaughterhouse, in the holy city of Makkah, during the Rev. sci. tech. Off. int. Epiz., 33 (3) 2 No. 22052014-00032-EN 2/26 pilgrimage season 1432 H (4-9 November 2011). In addition, blood samples were collected from 100 local work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…This represented a significant decline in small ruminants that were exposed to the virus. However, this decline may also be due to methodology, as a 2011 RVFV survey of 500 ruminants in a Mecca slaughterhouse showed that over 16% of sacrificial sheep and goats were seropositive using competitive ELISA [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This represented a significant decline in small ruminants that were exposed to the virus. However, this decline may also be due to methodology, as a 2011 RVFV survey of 500 ruminants in a Mecca slaughterhouse showed that over 16% of sacrificial sheep and goats were seropositive using competitive ELISA [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, 9·4% of camels in Khartoum State, Sudan, sampled during 2014-15 had had a Rift Valley fever virus infection as measured by IgG antibodies. 28 Furthermore, the main export market for Sudanese livestock is Saudi Arabia, just across the Red Sea from Port Sudan, 29 30 This fi nding indicates that Rift Valley fever virus could have been circulating among livestock in the Port Sudan region during the study period. Both Rift Valley fever virus and chikungunya virus are transmitted by mosquitoes, which increase in numbers during the warm periods that follow after heavy rainfall.…”
Section: Table 3: Association Between Rift Valley Fever Virus Positivmentioning
confidence: 89%
“…In Kenya and Somalia, RVF caused 478 human deaths in 1997 (14). In 2000, RVF outbreak was con rmed in Saudi Arabia and Yemen with 882 con rmed cases and 124 deaths (11). In the Sudan, serological evidence of RVF was reported in 1936 which revealed 6.7% of 164 human sera by using precipitating antibodies (7).…”
Section: Discussionmentioning
confidence: 99%